Ilmu Dhoruri Dalam Pengambilan Keputusan Hakim Di Dalam Perkara Kasus Pencurian - Saidah, Novica Erliyana Nur (Maliki Interdisciplinary Journal, 2025)
As a basic science that regulates the method of deriving law, ushul fiqh has an important role, especially for judges in making decisions. Judges do not only follow the legal text literally, but must also understand the context, objectives, and methodology so that the decisions taken can uphold justice and compliance with sharia. Dhoruri Science is knowledge that is obtained directly without going through a process of reasoning or in-depth analysis. In the context of Islamic law, Dhoruri Science has an important role in supporting judges in making decisions that are not only legal, but also fair and humane. This article discusses how Dhoruri Science is used by judges in handling theft cases, especially those involving minors. With a case study of a 13-year-old teenager in Jayapura who stole a motor vehicle, it is discussed how judges can consider the social background, age of the perpetrator, economic conditions, and real evidence as a basis for making decisions. This approach allows for the achievement of substantive justice that is in line with the values of maqasid al-shariah, such as protection of life, mind, descendants, and property. Dhoruri Science also encourages a more flexible justice system, responsive to the dynamics of society, and not trapped in rigid laws. Therefore, Dhoruri Science contributes greatly to creating a justice system that not only punishes, but also fosters and restores, especially for perpetrators who are still children. This study shows that the integration of Dhoruri Science in the legal decision-making process is important to maintain the balance between legal justice and social justice in contemporary Islamic society.